Brain, mind and linguistic processing insights into the dynamic nature of bilingualism and its outcome effects. (May 2021) - Di Pisa, Grazia; Pereira Soares, Sergio Miguel; Rothman, Jason
Highlights: Contextualizing the research field to which this special issue is contributing. Binding all the papers together for a better comprehension of the overall issue. Addressing the contemporary issues and debates surrounding bi-/multilingualism and the brain/mind, thereby providing a unique window into bilingual processing.